Testing a Human Antimicrobial RNase Chimera Against Bacterial Resistance - Prats-Ejarque, Guillem; Li, Jiarui; Ait-Ichou, Fatima; Lorente, Helena; Boix, Ester (Frontiers in Microbiology, 2019)
Emergence of bacterial resistance to most commonly used antibiotics urges the design of novel antimicrobial drugs. Antimicrobial proteins and peptides (AMPs) are key players of the host innate immunity. They exert a rapid and multifaceted action that reduces the development of bacterial adaptation mechanisms. Human antimicrobial RNases belonging to the vertebrate specific RNase A superfamily participate in the maintenance of tissue and body fluids sterility. Among the eight human canonical RNases, RNase 3 stands out as the most cationic and effective bactericidal protein against Gram-negative species. Its enhanced ability to disrupt the bacterial cell wall has evolved in detriment of its catalytic activity. Based on structure- functional studies we have designed an RNase 3/1 hybrid construct that combines the high catalytic activity of RNase 1 with RNase 3 bactericidal properties. Next, we have explored the ability of this hybrid RNase to target the development of bacterial resistance on an Acinetobacter baumannii cell culture. Synergy assays were performed in combination with colistin, a standard antimicrobial peptide used as an antibiotic to treat severe infections. Positive synergism was observed between colistin and the RNase 3/1 hybrid protein. Following, using an in-vitro experimental evolution assay, by exposure of a bacterial culture to colistin at incremental doses, we demonstrated the ability of the RNase 3/1 construct to reduce the emergence of bacterial antimicrobial resistance. The results advance the potential applicability of RNase-based drugs as antibiotic adjuvants.